Endoscopic Transnasal Odontoidectomy - Zoia, Cesare; Bongetta, Daniele; Luzzi, Sabino (Journal of Neurological Surgery Part B: Skull Base, 2020)
Background Odontoidectomy may represent the treatment of choice for symptomatic ventral craniovertebral junction stenosis in selected cases. An endoscopic transnasal approach has been proposed as an alternative to a classic transoral approach.Method We report a case of a patient with a craniovertebral junction stenosis due to the ossification of the posterior ligament. The clinical and radiological records of the patient and a step-by-step description of the surgical technique are presented (Fig. 1).Conclusion Endoscopic transnasal odontoidectomy provides a direct access to the dens and adjacent structures of the anterior upper cervical spine with a less invasive burden on the oropharingeal structures.The link to the video can be found at: https://youtu.be/Ofrk1sFTV9I.
Keywords: odontoidectomy; endoscopic transnasal surgery; endoscopic cervical decompression; craniovertebral junction